Understanding the role of different program components of a nutrition sensitive intervention in mediating impact: Applying causal mediation analysis to experimental evidence from Burkina Faso - Heckert, Jessica; Leight, Jessica; Awonon, Josué; Gelli, Aulo (International Food Policy Research Institute, 2021)
In complex nutrition-sensitive interventions, separately identifying the effect of each programmatic component on the outcomes of interest can be challenging. This paper examines the relationship between participation in different elements of the nutrition-sensitive intervention SELEVER, implemented in rural Burkina Faso with the objective of increasing poultry production and enhancing related nutritional outcomes, and women’s poultry production. We use structural equation modeling to estimate the direct effect of each component of program participation. Our findings suggest that respondents’ directly reported participation in SELEVER intervention activities mediates less than half of the observed intervention effects on poultry owned by women as well as women’s revenue and profits from poultry production. Accordingly, other indirect channels for program effects also seem to be important.